Multisensoryczność "Listów do Very" Vladimira Nabokova - Ginter, Anna (Acta Neophilologica, 2021)
The main aim of the present paper is to investigate and describe the nature of synaesthetic devices employed by Vladimir Nabokov evident in his letters to his wife – Vera Slonim. The analysis of the language and style of the matrimonial intimate correspondence, written for one reader only, is expected to provide evidence allowing one to establish whether the numerous variants of perceptual synaesthesia employed by Nabokov in all his literary texts reflect his genuine synaesthetic experiences or whether such can only serve as examples of the writer’s passion for creating a kind of perceptual play on words and puzzles.